Edukasi Penggunaan Sistem Informasi Permintaan Liputan Pada PT Cendrawasih Wiputra Mandiri - Tirsa Ninia Lina; Matheus Supriyanto Rumetna; Charliany Hetharia; Frenny Silvia Pormes; Joseph Eliza Lopulalan (Journal of Social Responsibility Projects by Higher Education Forum, 2022)
PT. Cendrawasih Wiputra Mandiri (CWM) having its address at Danau Maninjau Street, Rufei No. 19 Sorong City, is a cable TV and Channel company that has a lot of demand for coverage both in the Sorong City area and outside Sorong City. However, information about the process of requesting coverage is still not optimal, this causes many customers who often cancel the process of requesting coverage due to lack of information about the process of coverage. Therefore, PT. CWM needs to take advantage of the website for business development, especially in terms of information related to coverage request services. The use of the website must be maximized by PT. CWM, many employees of PT. CWM which has not been able to operate the website for coverage requests properly. For this reason, the Community Service (PkM) team needs to educate about the use of the website. Education is an important thing and really needs to be done because with education PT. CWM employees can work more optimally, especially in terms of operating a website for coverage requests. The education carried out by the PkM team had a huge impact, because apart from teaching how to operate a website, the PkM team also shared knowledge about how to solve problems related to using the website. The main purpose of this PkM activity is to share knowledge and care for others, especially to help PT. CWM to continue to innovate and survive during the pandemic